Activation and inhibition of the endogenous opioid system in human heart failure. Issue 1 (January 1995) - Oldroyd, K. G.; Gray, C. E.; Carter, R.; Harvey, K.; Borland, W.; Beastall, G.; Cobbe, S. M.
Abstract : BACKGROUND--In a canine model of congestive heart failure beta endorphin concentrations were high and opioid receptor antagonists exerted beneficial haemodynamic effects. In humans previous studies have suggested that opioid peptides may modify the perception of breathlessness and fatigue in heart failure. METHODS--Plasma concentrations of beta endorphin were measured in patients with acute and chronic heart failure and cardiogenic shock. A subgroup of eight patients with New York Heart Association (NYHA) class III-IV heart failure was assessed for acute haemodynamic effects of naloxone, an opioid receptor antagonist. A separate group of 10 patients with class II-III heart failure, was randomised to a double blind placebo controlled study of the effects of intravenous naloxone on cardiopulmonary exercise performance. RESULTS--Plasma concentrations of beta endorphin were usually normal in patients with chronic heart failure and did not correlate with severity as assessed by NYHA class. In 29% of patients with acute heart failure and 71% of those with cardiogenic shock beta endorphin concentrations were high. The median concentration in the cardiogenic shock group was significantly higher than in either of the two heart failure groups and there was some evidence of a relation between beta endorphin concentrations and survival. At the doses tested, naloxone was unable to modify systemic haemodynamics, exercise performance, or symptoms in patients with chronic congestive heart failure. CONCLUSIONS--Circulating concentrations of beta endorphin are usually normal in patients with chronic congestive heart failure. Inhibition of the endogenous opioid system is unlikely to have therapeutic potential in heart failure.